Editorial: Covid-19 Pandemic and International Tourism Demand - Haryanto, Tri (Universitas Airlangga, 2020)
COVID-19 pandemic has become a global issue. Many experts predict that this pandemic will cause global economic growth to decline this year, or even the global economic recession. All efforts conducted by many countries in the world massively to prevent its spread such as social distancing, self-isolation, and similar actions to lockdown may have a major impact on tourism demand in many countries. The next section sequentially will discuss a brief review of the role of international tourism on the economy, the impact of the COVID-19 pandemic on the global economy and international tourism, and further research topics for the next edition.